Fish silage in farm-made feed for Nile tilapia - Abimorad, Eduardo Gianini; Strada, Wilson Luiz; Schalch, Sérgio Henrique Canelo; Garcia, Fabiana; Castellani, Daniela; Manzatto, Marcelo da Rocha (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this work was to evaluate the use of a farm-made feed based on silage of fish filleting residues for Nile tilapia (Oreochromis niloticus) farming. Two thousand and seventy masculinized tilapia juveniles (83.1 g) were distributed into six ponds (230 m2), at a stocking density of 1.5 fish per square meter. The experimental design was a completely randomized with two treatments (farm-made and commercial feeds) and three replicates. The performance parameters analyzed were survival, weight gain, apparent feed conversion, specific growth rate, and final weight coefficient of variation. The water quality variables analyzed were dissolved oxygen, transparency, and total phosphorus and nitrogen. Feeding cost and body composition were also evaluated. No significant differences were observed in the performance parameters. Water eutrophication in the ponds with farm-made feed was higher than in ponds with commercial feed. The cost of fish produced using farm-made feed (R 1.07 kg-1) was approximately 42% lower than the cost of fish produced using commercial feed (R 1.86 kg-1). Fish fed with farm-made feed had lower lipid body content than fish fed with commercial feed.